18 - CORRELATION BETWEEN THE TIME OF STAY IN HEMODIALYSIS AND EXERCISE CAPACITY (Fiep Bulletin - online, 2011)
Introduction: The characteristics of exercise intolerance of patients with CKD are still largely unexplored and has not been established. The low exercise tolerance and physical deconditioning, although not fully understood in this population is by factors of negative multifactorial and complex. Objective: To correlate exercise capacity of patients with Chronic Kidney Disease (CKD) on dialysis, with time spent in hemodialysis patients with chronic renal failure, providing scientific information to professionals in this specialty in order to better establish the evaluation criteria and rehabilitation for this população. Métodos: We analyzed 30 patients (17 men) with mean age 46.8 ± 12 years, duration of dialysis was 50.6 ± 40 months and kt / V of 1.2 ± 0.2 ; on dialysis for at least 3 months. The exercise capacity was assessed by the distance walked in six minutes (DP6min) analysis and indirect maximum oxygen consumption (VO2max) by means of the Shuttle Walk Test (SWT), made in interdiálise. Statistical analysis of quantitative variables, the results were expressed as means and standard deviations. To correlate the time spent on hemodialysis and exercise capacity, we used the Pearson's coefficient. Statistical significance was set to ? = 5% (p
Keywords: exercise capacity; chronic renal disease; hemodialysis